Digitalised validation systems as an enabler for quality 4.0 within a medical device manufacturer - Olivia McDermott; Neasa Conroy; M. Thenarasu; Susana Duarte (Sustainable Futures)
Purpose: This research examines the implementation challenges and benefits of transitioning to a paperless validation system as part of a Quality 4.0 initiative within a Medical Device manufacturer in order to address a gap related to such studies in the literature. Methodology: This research was conducted using a case study executed in a large medical device manufacturing facility. The study followed the successful implementation of a digitalised validation system using the Design for Six Sigma methodology to move away from a heavily paper-based validation process as part of the site Quality 4.0 strategy. Findings: Digitalised validation systems have benefits, including more sustainable processes with the elimination of paper, a streamlined review and approval process, and the successful management of data integrity for large volumes of validation data while also decreasing opportunities for audit findings. The challenges encountered by the site during implementation were ensuring end users of these systems had adequate training, overcoming resistance to change, upskilling, and maintaining well-managed change communication. Limitations/Implications: This study was conducted at a single site, but the research enables documentation of an unprecedented longitudinal case study conducted over a 2-year implementation and 1-year post-implementation period and gives unprecedented insight into the practical challenges of deploying paperless validation systems in a large medical device manufacturer. The study also makes a contribution to knowledge sharing within the Medtech industry. Originality/Value: This research project is one of the first longitudinal studies in a large medical device manufacturer to document a Quality 4.0 case study around transitioning to a paperless validation system in a regulated industry and thus fulfils a gap in the literature. Medtech professionals can leverage the work to benchmark the challenges and benefits of paperless validation in maintaining and improving regulatory compliance, quality, environmental sustainability and employee morale.